2019
DOI: 10.1108/ijse-12-2018-0673
|View full text |Cite
|
Sign up to set email alerts
|

Do remittances promote human development? Empirical evidence from developing countries

Abstract: Purpose The purpose of this paper is to analyse the impact of remittances on human development in developing countries using panel data from 1980 to 2014 and to address the critical question of whether the increasing trend of remittances has any impact on human development in a broad range of developing countries. Design/methodology/approach Usual panel estimates, such as pooled OLS, fixed or random effects model, possess specification issues such as endogeneity, heterogeneity and measurement errors. In this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 50 publications
5
18
0
Order By: Relevance
“…Remittances from abroad are found to have a statistically significant and positive impact on poverty alleviation only for upper middle-income countries (Azam et al (2016) while Simiyu et al (2018) found that there were significant welfare and poverty level differences between remittance recipient and non-recipient households. Besides, Huary and Bani (2017) found that a 1 per cent increase in remittances decreases the poverty headcount by 0.41 per cent. Waheed et al (2013) found that a 10 per cent increase in domestic remittances decreased poverty incidence, poverty gap and squared poverty gap by 1.80 per cent, 1.60 per cent and 1.60 per cent while 10 per cent rise in foreign remittances reduced poverty incidence, poverty gap and squared poverty gap by 0.86 per cent, 0.62 per cent and 0.62 per cent respectively in rural Nigeria.…”
Section: Review Of Literaturementioning
confidence: 98%
“…Remittances from abroad are found to have a statistically significant and positive impact on poverty alleviation only for upper middle-income countries (Azam et al (2016) while Simiyu et al (2018) found that there were significant welfare and poverty level differences between remittance recipient and non-recipient households. Besides, Huary and Bani (2017) found that a 1 per cent increase in remittances decreases the poverty headcount by 0.41 per cent. Waheed et al (2013) found that a 10 per cent increase in domestic remittances decreased poverty incidence, poverty gap and squared poverty gap by 1.80 per cent, 1.60 per cent and 1.60 per cent while 10 per cent rise in foreign remittances reduced poverty incidence, poverty gap and squared poverty gap by 0.86 per cent, 0.62 per cent and 0.62 per cent respectively in rural Nigeria.…”
Section: Review Of Literaturementioning
confidence: 98%
“…This implies that increasing government expenditure will significantly reduce the proportion of individual below poverty line by about percent. The findings of these five studies is however inconsistent with Huay et al, (2019), Kaidi and Mensi (2019).…”
Section: Federalism Structure and Government Expenditure Trend In Nigmentioning
confidence: 79%
“…Applying System generalized method of moment (Sys-GMM), Huay et al, (2019) 2019, Kaidi and Mensi (2019) found that one percent growth in government consumption expenditure leads to a 0.10 percent decline in private consumption in examined ECOWAS countries. This is an indication of crowing out effect in the long-run and short-run periods.…”
Section: Federalism Structure and Government Expenditure Trend In Nigmentioning
confidence: 99%
“…This implies that increasing government expenditure will significantly reduce the proportion of individual below the poverty line by about 7%. The findings of these five studies are however inconsistent with Huay et al (2019) and Kaidi and Mensi (2019).…”
Section: Brief Review Of Relevant Literaturementioning
confidence: 79%
“…Applying the system generalized method of moment (Sys-GMM), Huay et al (2019) investigated the impact of remittances on human development in 66 developing countries from 1980 to 2014 by incorporating government expenditure in the model. The significant but negative coefficient of government expenditure means that, when other variables are held constant, increased government expenditure rather than serve as a human development catalyst reduces it.…”
Section: Brief Review Of Relevant Literaturementioning
confidence: 99%